Pengaruh Umur Terhadap Keaktifan Lansia Pada Posyandu Lansia - Sitaresmi, Sandra Dewi; Safriana, Rizka Esty (IJMT : Indonesian Journal of Midwifery Today, 2022)
ABSTRACT Elderly is a condition characterized by a person's failure to maintain a balance against physiological stress conditions. Often the elderly and those around them cannot accept the changes and setbacks that occur so that it will cause problems for the elderly such as neglect. The purpose of this study was to determine the effect of age on the activity of the elderly at Integrated Healthcare Centerfor the elderly in Waung Village, Boyolangu District, Tulungagung Regency. This study uses an analytic study, the type of observational research with a case control design. The sample of this study was the elderly of Waung village, Boyolangu district, Tulungagung district in 2022 as many as 23 people. The research sample was taken using a non-probability sampling technique with total sampling type. The data obtained were then analyzed using the chi square test and the results obtained that the value of p = 0.078 means that it is not significant because it is more than 0.05. The conclusion of the research shows that there is no influence of the age of the elderly on the activity of participating in the Integrated Healthcare Center for the elderly in Waung Village.